Developing a Heart Transplantation Self-Management Support Mobile Health App in Taiwan: Qualitative Study - Chen, Yi-Wen; Wei, Jeng; Chen, Hwei-Ling; Cheng, Ching-Hui; Hou, I-Ching (JMIR Publications, 2020)
BackgroundHeart transplantation (HTx) is the most effective treatment for end-stage heart failure patients. After transplantation, patients face physiological, psychological, social, and other health care problems. Mobile health (mHealth) apps can change the delivery of conventional health care to ubiquitous care and improve health care quality. However, a dearth of mHealth apps exists for patients with HTx worldwide, including in Taiwan. ObjectiveThe aim of this study was to investigate the information needed and to develop a preliminary framework for an mHealth app for post-HTx patients. MethodsA qualitative approach with individual in-depth interviews was conducted at a heart center in the regional hospital of northern Taiwan from June to November 2017. Patients that had undergone HTx and their health professionals were recruited for purposeful sampling. A semistructured interview guideline was used for individual interviews and transcribed. Thematic analysis was used for data analysis. ResultsA total of 21 subjects, including 17 patients and 4 health professionals, were recruited for the study. The following five major themes were identified: reminding, querying, experience sharing, diet, and expert consulting. Minor themes included a desire to use the app with artificial intelligence and integration with professional management. ConclusionsAn intelligent mHealth app that addresses the five main themes and integrates the processes of using a mobile app could facilitate HTx self-management for Taiwanese patients.